Turkey, China and the silk road of energy :|The Trans-Anatolian natural gas pipeline - Akar, Zeynepcan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis analyzes the motives behind involvement of Turkey and China in the Trans-Anatolian Natural Gas Pipeline (TANAP). Referred as the Silk Road of Energy, TANAP is a fundamental section of Southern Gas Corridor which is an international new route for diversifying energy sources of Europe. TANAP is a recently constructed pipeline crossing Turkey and will carry 16 bcm of natural gas of Azerbaijan delivered from Shah Deniz 2 field, 6 bcm of which will be consumed in Turkish national market and the rest will be transferred to Europe. As an international project, TANAP received loans from various institutions, while World Bank and Asian Infrastructure Investment Bank (AIIB) are co-financing the project. As a newly established institution spear-headed by China in 2015, AIIB aims to support infrastructure development in Asia, while TANAP is a section of a new energy route benefiting Europe, which is not directly within the spectrum of AIIB. Even though not directly involved, China imposes a role in TANAP through AIIB. The involvement of China through the loan provided by AIIB implies China’s interest in this new energy route and is a subtle cooperation between Turkey and China on future energy relations. On the other hand, TANAP is a significant part of Turkey’s aim to become an energy hub and highlights Turkey’s strategic position between Asia and Europe while complimenting Turkey’s energy security. The motives of Turkey are both strategic and energy security based while China has only strategic motives in involving in TANAP.
Keywords: Energy industries -- China.; Energy industries -- Turkey.; Energy policy -- China.; Energy policy -- Turkey.; Geopolitics -- Turkey.; China -- Relations -- Turkey; Turkey -- Relations -- China.